Formulation and in vitro evaluation of topical nanosponge-based gel containing cassia alata leaves extract - MANEESH SHAKYA; NEERAJ PATIDAR; UMESH KUMAR JAIN (International Journal of Multidisciplinary Research and Studies, 2024)
This abstract describes the formulation and in vitro testing of a topical nanosponge-based gel containing Cassia alata leaf extract, which is known for its powerful antibacterial capabilities. Active metabolites such alkaloids, flavonoids, glycosides, steroids, tannins, and phenols were discovered through qualitative phytochemical screening. Quantitative experiments measured total phenolic content (TPC) and total flavonoid content (TFC) using gallic acid and rutin as standards. Nanosponges made of ethyl cellulose and polyvinyl alcohol (PVA) showed promising drug transport properties. Scanning electron microscopy (SEM) validated the nanosponges' porous, spherical form, with an average particle size of 521.2 nm and a consistent zeta potential of 69.7 mV. The produced nanosponge gel had excellent viscosity, pH, and spreadability, which aided in drug release and permeability. Notably, the nanosponge formulation enhanced the Cassia alata extract's antibacterial efficacy against E. coli. The superior performance of the 1 mg/ml nanosponge gel highlights its potential for more effective bacterial infection treatment. The findings indicate that Cassia alata nanosponges may improve medication solubility and bioavailability, making them a good candidate for skin disease treatment, with the added benefits of lower dosage, administration frequency, and side effects.